High mobility group box 1 is involved in the pathogenesis of passive transfer myasthenia gravis model. Issue 9 (9th June 2021) - Maimaitiming, Bibinu; Uzawa, Akiyuki; Ozawa, Yukiko; Yasuda, Manato; Kojima, Yuta; Kanai, Tetsuya; Kuwabara, Satoshi
Abstract : Myasthenia gravis (MG) is an autoimmune disease with autoantibodies against the mainly nicotinic acetylcholine receptor (AChR). High mobility group box1 (HMGB1) acts as a danger signal and drives the pathogenesis of autoimmune-mediated diseases. However, the role of HMGB1 in the pathogenesis of MG is not fully understood. Therefore, in this study, we analyzed serum levels of HMGB1 and immunohistochemical HMGB1 staining of muscle tissues in the passive transfer MG model to investigate the role of HMGB1 in MG. As a result, serum HMGB1 levels tended to be higher and the quantitative score of muscle pathology showed greater HMGB1 deposition ( P = 0.02) along with sparser AChR staining and more severe inflammation in the passive transfer MG rats ( n = 6) than those in control rats ( n = 6). These findings indicate that HMGB1 is an important mediator and biomarker for inflammation in the pathogenesis of MG and can be a therapeutic target in MG.